EXPONENTIAL EQUATION AND INEQUALITIES - Kengashev Umidjan Tashbekovich (Web of Journals Publishing, 2025)
This article covers points on the properties of exponential equations and inequalities as well as methods of solving.
Keywords: Equation, exponential equation, exponential inequality, logarithming, graphical method, exchange.